Extended Thromboprophylaxis in Hospitalized Patients with Heart Failure: A Post Hoc Analysis of the MAGELLAN Study - Spyropoulos, Alex C.; Raskob, Gary E.; Spiro, Theodore E.; Lu, Wentao; De Sanctis, Yoriko; Albanese, John; Mebazaa, Alexandre; Barnathan, Elliot S. (TH Open, 2022)
This post hoc subgroup analysis examined efficacy and safety outcomes with extended thromboprophylaxis rivaroxaban compared with in-hospital enoxaparin in 2,078 patients from the MAGELLAN study who had a hospitalization for heart failure or a history of heart failure and a lower risk of bleeding. A significant 36% reduction in the composite endpoint of asymptomatic proximal deep vein thrombosis (DVT) in the lower extremity, symptomatic DVT in the lower extremity (proximal or distal), symptomatic nonfatal pulmonary embolism, and venous thromboembolism-related death was observed with rivaroxaban. Major bleeding was low in both groups and not significantly increased with rivaroxaban.
Keywords: heart failure; thrombosis; rivaroxaban; direct oral anticoagulants; venous thromboembolism; medically ill